HUBUNGAN ANTARA KEMAMPUAN REFLEKSI DIRI DAN PROFESIONALISME MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA - , LISA RIFANI; , dr. Rahmadya Nur Hidayah, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Physician expertise conceptualized in clinical competence that embedded in the personal and professional competence in a broad spectrum. Complexity that inherent in clinical practice, requires not only the skilled behavior that is also type of clinical reasoning and reflection of the latest scientific, and personal reflection. Reflection is considered as a central part of teaching and learning in a profession. It is necessary to study whether there is a relationship between the ability of self-reflection and professionalism. Objective : To understand relationship between selfreflection and professionalism in Faculty of Medicine Gadjah Mada University. Method : The research was conducted in quantitative research with cross-sectional research design. Subjects were 168 medical students year 2008 Faculty of Medicine Gadjah Mada University both reguler and international programs. Results : In this study showed that students was included in the very high reflection category. Faculty of medicine students year 2008 are also included in high category for the level of professionalism. The analysis of the relationship between self-reflection and professionalism showed that there was no correlation between self-reflection and professionalism of the students of the Faculty of Medicine, Gadjah Mada University. Conclusion : In this study it can be concluded that there is no relationship between the frequency of selfreflection and higher professionalism.